ANALYSIS OF SMART CITY INITIATIVES TO SUPPORT ENVIRONMENTAL SUSTAINABILITY IN ASIA - Junaidi, Wendy (Jurnal Keuangan dan Bisnis, 2024)
This study aims to provide strategic insights into implementing smart city initiatives to support environmental sustainability, enabling local governments in developing countries to manage the complexity of smart cities through the Internet of Things (IoT) technology. The study focuses on several smart city cases in Asia, including Jakarta (Indonesia), Da Nang (Vietnam), Tokyo (Japan), and Lusail (Qatar). It utilizes in-depth interviews with IT vendor management and business consultants involved in smart city projects, along with a review of government documentation. Findings identify planning phases, partnerships, technology selection, implementation, and evaluation as key priorities. Smart city initiatives transform targeted areas or even entire cities, thus requiring collaboration among local governments, technology providers, academics, and citizens for successful implementation. Governments need to adjust regulatory frameworks, including data ownership, environmental standards, and security. The private sector should stay updated on regulatory developments to ensure compliance before market entry.